2004
DOI: 10.1002/mds.20061
|View full text |Cite
|
Sign up to set email alerts
|

Differences in age at onset and familial aggregation between clinical types of idiopathic Parkinson's disease

Abstract: Idiopathic Parkinson's disease (PD) can be subdivided by its patterns of motor symptoms into tremor-dominant (TDT), akinetic-rigid (ART), and mixed type (MT). Our objective was to determine whether age at onset and family history are different in these three types. In total, 366 patients with PD were assigned in a standardized approach to one of the three subtypes. Age at onset and family history were obtained in all patients and all presumably affected family members were examined. Mean ages at disease onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 46 publications
3
40
0
1
Order By: Relevance
“…The familial aggregation was stronger for early-onset compared to late-onset PD, although definitions of early and late varied across studies [134,138,148,149,157,158,[161][162][163]. Most studies that examined different types of relationships (siblings or parent-child) reported that PD in a sibling was associated with a higher risk compared to PD in a parent or child [131,[161][162][163][164], indicating recessive genetic or shared environmental effects.…”
Section: Family Studiesmentioning
confidence: 99%
“…The familial aggregation was stronger for early-onset compared to late-onset PD, although definitions of early and late varied across studies [134,138,148,149,157,158,[161][162][163]. Most studies that examined different types of relationships (siblings or parent-child) reported that PD in a sibling was associated with a higher risk compared to PD in a parent or child [131,[161][162][163][164], indicating recessive genetic or shared environmental effects.…”
Section: Family Studiesmentioning
confidence: 99%
“…They represented the control group of a larger study on walking in Idiopathic Parkinson's Disease (IPD), a motor disorder where loss of gait-related arm swing is a prominent sign (Buchthal and Fernandez-Ballesteros 1965). The subjects' average age was 61.4 years ± 5 (SD), which corresponds to the average age of onset of IPD (see Korchounov et al 2004). The inclusion criteria were absence of neurological, orthopedic, and cardio-respiratory diseases, upper and lower limb prostheses, and gait disorders.…”
Section: Subjectsmentioning
confidence: 99%
“…1,2 Moreover, although the core features for diagnosing PD are resting tremor, bradykinesia, rigidity, and postural instability, there is great variability in the clinical presentation of individual patients, suggesting the existence of subtypes of the disease with differences in clinical pattern, pathogenesis, and disease progression. [3][4][5][6] In particular, a tremor-dominant type is usually distinguished from an akinetic-rigid type. [5][6][7] Neuroimaging techniques, including voxel-based morphometry, [8][9][10][11][12] proton MR spectroscopy, 13,14 positron-emission tomography (PET), [15][16][17][18] and single-photon emission tomography [19][20] demonstrate widespread changes in the cerebral hemispheres in patients in advanced clinical stages of PD.…”
mentioning
confidence: 99%
“…[3][4][5][6] In particular, a tremor-dominant type is usually distinguished from an akinetic-rigid type. [5][6][7] Neuroimaging techniques, including voxel-based morphometry, [8][9][10][11][12] proton MR spectroscopy, 13,14 positron-emission tomography (PET), [15][16][17][18] and single-photon emission tomography [19][20] demonstrate widespread changes in the cerebral hemispheres in patients in advanced clinical stages of PD. Recently, several studies pointed out the capability of the histogram analysis of the apparent diffusion coefficient computed from diffusion-weighted images and of the mean diffusivity and fractional anisotropy (FA) computed from diffusion tensor imaging (DTI) to reveal brain-tissue damage in neurodegenerative diseases with predominant involvement of the gray matter (GM), such as Alzheimer disease, 21 Huntington disease, 22 and progressive ataxias.…”
mentioning
confidence: 99%